Adenosine pathway inhibitors: novel investigational agents for the treatment of metastatic breast cancer. (3rd July 2022) - Rizzo, Alessandro; Massafra, Raffaella; Fanizzi, Annarita; Rinaldi, Lucia; Cusmai, Antonio; Latorre, Agnese; Zaccaria, Gian Maria; Ronchi, Maria; Telegrafo, Michele; Gadaleta-Caldarola, Gennaro; Giotta, Francesco; Lorusso, Vito; et al.
ABSTRACT: Introduction: The adenosine pathway has been suggested to play a key role in several carcinogenetic processes, with the metabolism of adenosine-5′-triphosphate (ATP) and its derivatives reported to be dysregulated in breast cancer. Preclinical evidence has supported the role of adenosine in the pathogenesis of this malignancy as well as the development of selective adenosine pathway inhibitors. Areas covered: The paper overviews the evidence regarding the use of adenosine pathway inhibitors in breast cancer; a literature search was conducted in January 2022 of Pubmed/Medline, Cochrane library, and Scopus databases. Expert Opinion: The adenosine pathway regulates inflammation, apoptosis, metastasis, and cell proliferation in breast cancer cells, and adenosine pathway inhibitors have yielded encouraging results in early-phase clinical trials. Well-designed, multicenter studies focused on monotherapies and combination therapies (which include immune checkpoint inhibitors) are warranted in this setting.